2021
DOI: 10.1111/cns.13640
|View full text |Cite
|
Sign up to set email alerts
|

Combining chitin biological conduits with small autogenous nerves and platelet‐rich plasma for the repair of sciatic nerve defects in rats

Abstract: Aims Peripheral nerve defects are often difficult to recover from, and there is no optimal repair method. Therefore, it is important to explore new methods of repairing peripheral nerve defects. This study explored the efficacy of nerve grafts constructed from chitin biological conduits combined with small autogenous nerves (SANs) and platelet‐rich plasma (PRP) for repairing 10‐mm sciatic nerve defects in rats. Methods To prepare 10‐mm sciatic nerve defects, SANs were first harvested and PRP was extracted. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Among them, chitosan, widely found in nature and extracted from insects’ shells, is the product of chitin-N-deacetylation. Its good plasticity makes it commonly used to prepare 3D spherical microcarriers [ 26 , 47 ]. The diameter, pore size, and porosity of the microcarriers can be adjusted according to demand by controlling the concentration of the liquid and oil phases, the volume ratio of the oil phase to the water phase, and the stirring rate [ 28 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, chitosan, widely found in nature and extracted from insects’ shells, is the product of chitin-N-deacetylation. Its good plasticity makes it commonly used to prepare 3D spherical microcarriers [ 26 , 47 ]. The diameter, pore size, and porosity of the microcarriers can be adjusted according to demand by controlling the concentration of the liquid and oil phases, the volume ratio of the oil phase to the water phase, and the stirring rate [ 28 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…By suturing the nerves at both ends with minimal tension, the occurrence of local neuromas and secondary neuralgia can be significantly reduced. Furthermore, the technique maintains the gaps between nerve stumps, and research has indicated that the regrowth of axons is associated with the distance separating the nerve stumps [ 45 , 46 ]. In previous studies, we found that nerve regeneration was relatively better when the regeneration gap in rat peripheral nerves was 1–2 mm [ 8 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Twelve weeks post-operation, the sciatic nerve functional index, compound action potential amplitude, myelinated nerve fiber density, and myelin thickness all significantly increased. The density of sensory and motor neurons in the motor endplates of the group treated with chitin bioconduits loaded with SAN and PRP was higher than in the group treated with only one of them (PRP or SAN), indicating that chitin conduits simultaneously loaded with SAN and PRP had better repair effects ( 61 ).…”
Section: Efficacy Of Novel Biomaterials In Peripheral Nerve Injurymentioning
confidence: 99%